Enriching Students' Perspectives in Solving Life's Problems through Chemical Learning - Winarni, Sri; Syahrial, Syahrial (Universitas Sebelas Maret, 2020)
The chemistry benefits will be felt directly if the learning process is based on close problems in students' lives. The chemistry can help students solve life problems. The purpose of this paper is mapping a number of student life problems that have been reported by several previous researchers. The review results are expected to help chemistry teachers in implementing problem solving in the classroom. Problems that are solved on problem solving in chemistry learning must meet the following four criteria: (1) the solution requires a chemical concept; (2) comes from everyday life; (3) demands to take a position and decision; and (4) the possibility of different perspectives in solving it. There are seven points of view found from the analysis of the article. Seven points of view in solving life's problems, namely: (1) character / value, (2) psychological; (3) health; (4) environment; (5) economy; (6) mathematics; and (7) daily work. These seven aspects can be used by the teacher as learning basis in the introduction, core activities, and evaluation.